Fits Like a Glove: Seinfeld and the Economics of Liability Laws - Franklin G. Mixon Jr.; Shane D. Sanders; R. Andrew Luccasen III (American Business Review)
Informal case applications often enhance our understanding of an economic principle’s breadth of import in everyday life, as well as whether the principle may be acknowledged and used in a manner that facilitates decision-making of businesses and consumers. The present study contributes to the case study literature by extending the work of others on the economics of the classic television sit-com, Seinfeld. More specifically, our extension focuses on several law and economics concepts, particularly concepts related to product liability, included in the sit-com that are of particular interest to businesses and consumers.